2019
DOI: 10.1111/ecc.13016
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of health sciences students about colorectal cancer risk factors

Abstract: Objective This descriptive study was conducted in order to determine the risk factors, symptoms and awareness of health sciences students with regards to colorectal cancer (CRC). Methods This study included 1,028 health science students from two different universities. Data for this study were collected via a questionnaire form that included questions about CRC risk factors, protective approaches and symptoms. Frequencies, percentages and averages of the data were assessed with Kruskal–Wallis and Mann–Whitney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In addition, fish, fibers, and milk consumption reduce the risk of colon cancer [ 39 ]. Among students, the most important factors for CRC development are smoking (90.5%), excessive alcohol consumption (87.4%), family history of cancer (84.2%), and obesity (82.6%) [ 40 ]. The results of a prospective study regarding the effect of diet on CRC development were published in 2020.…”
Section: Risk Factors In Crcmentioning
confidence: 99%
“…In addition, fish, fibers, and milk consumption reduce the risk of colon cancer [ 39 ]. Among students, the most important factors for CRC development are smoking (90.5%), excessive alcohol consumption (87.4%), family history of cancer (84.2%), and obesity (82.6%) [ 40 ]. The results of a prospective study regarding the effect of diet on CRC development were published in 2020.…”
Section: Risk Factors In Crcmentioning
confidence: 99%
“…2 A). Previous studies have demonstrated that some factors such as age, sex, BMI, the history of smoking, drinking, and familial inheritance could increase the risk of CRC [ 57 61 ]. Therefore, before the comparison of serum derived exosomal hsa-circ-0004771 levels between different groups, we first confirmed that the risk factors mentioned above (the baseline data) were not different between the groups (Table 1 ), which guaranteed the uniformity between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the data conducted by the authors of the present study showed a statistically significant difference between the number of correctly given answers in the area of knowledge of CRC symptoms and the type of university attended by the students surveyed (medical, non-medical). In a study by Ustundag et al [ 39 ], health sciences students included blood in the stool ( n = 750; 73%), rectal bleeding ( n = 743; 72.3%), unintentional weight loss ( n = 686; 66.7%) and fatigue ( n = 656; 63.8%) among the most common symptoms of CRC. The problem of altered bowel frequency, including diarrhea and constipation, was indicated by 53.2% of respondents ( n = 547).…”
Section: Discussionmentioning
confidence: 99%